2006
DOI: 10.1002/app.24192
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparative hemostatic studies of chitin, chitosan, and their derivatives

Abstract: ABSTRACT:The effects of chitin, chitosan, and their derivatives on in vitro human blood coagulation and platelet activation were comparatively studied. The coagulation was assessed by the measure of the whole blood clotting time (WHBCT) and plasma recalcification time (PRT). The tested materials were chitin, chitosan, partially N-acetylated chi- -(2-hydroxy)propyl-3-trimethylammonium chitosan chloride, and SPONGOSTAN ® standard (a positive control). The results revealed that the WHBCTs of whole blood mixed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 19 publications
2
41
0
Order By: Relevance
“…It has reported that the activation of blood factor XII that potentiates the intrinsic pathway of blood plasma coagulation occurs efficiently in contact with hydrophilic procoagulants [35][36][37], due to specific binding event between factor XII. In the normal contact activation of the clotting cascade, factor XII termed Hageman factor is activated on contact with negatively charged surfaces [38]. The negatively charged surface probably readily induced the contact activation of clotting proteins and initiated the clotting cascade, resulting in the quick formation of fibrin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has reported that the activation of blood factor XII that potentiates the intrinsic pathway of blood plasma coagulation occurs efficiently in contact with hydrophilic procoagulants [35][36][37], due to specific binding event between factor XII. In the normal contact activation of the clotting cascade, factor XII termed Hageman factor is activated on contact with negatively charged surfaces [38]. The negatively charged surface probably readily induced the contact activation of clotting proteins and initiated the clotting cascade, resulting in the quick formation of fibrin.…”
Section: Resultsmentioning
confidence: 99%
“…The rougher surface and polymer chain influences the interfacial reaction of solute molecules with the chitosan surface. To understand the clotting effect on the surface more deeply, the surface analysis using scanning electron microscopy is seemed to be useful in the measurement of blood clotting time [38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…Its physical and biochemical properties can be further tailored to meet conditions in wound healing applications (Alves & Mano, 2008;Berger et al, 2004;Florea et al, 2006;Patois et al, 2009;Schuetz et al, 2008). Beside numerous chitosan derivatives, trimethyl chitosan (TMC), N-carboxymethyl chitosan (CMC) and O-carboxymethyl-N,N,N-trimethyl chitosan (CMTMC) have been synthesized, raising increasing interest due to their enhanced solubility, antibacterial activity, ability to complex drugs or DNA (Thanou et al, 2002), and good biocompatibility (Chen et al, 2006;Hansson et al, 2012a;Janvikul et al, 2006). The mechanism of action in the promotion of wound healing by chitosan derivatives is still debated but is suggested to depend on the type of functionalization.…”
Section: Figure 1 Wound Classification (Kyriacos Et Al 2008)mentioning
confidence: 99%
“…Chitosan-based wound dressings possess a set of unique properties, including haemostatic (Janvikul et al, 2006), biodegradable (Patois et al, 2009), and antibacterial properties (Agnihotri et al, 2004) that make them useful for wound healing. Chitosan's antibacterial activity was already observed at low concentrations against a variety of pathogens such as E. coli or S. aureus (Felt et al, 2000) and may be used in various formulation types such as gels (Yan et al, 2010), films (Mizuno et al, 2003) or nanoparticles (Hansson et al, 2012a).…”
Section: Chitosan Formulationsmentioning
confidence: 99%
See 1 more Smart Citation